2009
DOI: 10.1038/onc.2009.281
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 molecular chaperones are required to support p53 tumor suppressor activity under stress conditions

Abstract: p53 as an unstable protein in vitro likely requires stabilizing factors to act as a tumor suppressor in vivo. Here, we show that in human cells transfected with wildtype (WT) p53, Hsp90 and Hsp70 molecular chaperones maintain the p53 native conformation under heat-shock conditions (42 1C) as well as assist p53 refolding at 37 1C, during the recovery from heat shock. We also show that the interaction of WT p53 with WAF1 promoter in cells is sensitive to Hsp70 and Hsp90 inhibition already at 37 1C and further de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 47 publications
4
75
0
3
Order By: Relevance
“…Further, in vivo studies using firefly luciferase as a model substrate have documented the role of Hsp90 in protecting the proteins during stress and its role in refolding of non-native structures and degradation of terminally misfolded proteins during recovery from stress (Schneider et al, 1996). Hsp90-HOP, together with Hsp70-Hsp40 functions as a folding machine, also called foldosome that participates in the refolding of stress-denatured proteins during the recovery phase and prevents aggregation of misfolded proteins (Hutchison et al, 1994;McClellan et al, 2007;Powers et al, 2008;Schumacher et al, 1996;Walerych et al, 2009;Wegele et al, 2006). The Hsp90 reservoir, besides buffering proteostasis against environmental stress, is also involved in safeguarding protein functions in context of genetic variation.…”
Section: Ii41122 the Hsp90 Chaperone Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in vivo studies using firefly luciferase as a model substrate have documented the role of Hsp90 in protecting the proteins during stress and its role in refolding of non-native structures and degradation of terminally misfolded proteins during recovery from stress (Schneider et al, 1996). Hsp90-HOP, together with Hsp70-Hsp40 functions as a folding machine, also called foldosome that participates in the refolding of stress-denatured proteins during the recovery phase and prevents aggregation of misfolded proteins (Hutchison et al, 1994;McClellan et al, 2007;Powers et al, 2008;Schumacher et al, 1996;Walerych et al, 2009;Wegele et al, 2006). The Hsp90 reservoir, besides buffering proteostasis against environmental stress, is also involved in safeguarding protein functions in context of genetic variation.…”
Section: Ii41122 the Hsp90 Chaperone Systemmentioning
confidence: 99%
“…It could be due to the direct effect of 17-AAG on the folding machinery of cells. Hsp90 has been shown to co-operate with Hsp70-Hsp40 via the co-chaperones such as HOP in refolding stress-denatured proteins and in preventing misfolded proteins to form aggregates (Hutchison et al, 1994;McClellan et al, 2007;Powers et al, 2008;Schumacher et al, 1996;Walerych et al, 2009;Wegele et al, 2006). Additionally, Hsp90 inhibition has been shown to induce transcription of HSPs by HSF1 mediated activation (Sittler et al, 2001).…”
Section: Vi2 Assessment Of Folding Capacity Of Cells Using Fluc-basmentioning
confidence: 99%
“…Several clinical trials have been based on strategies to reintroduce wildtype P53 copies into cancerous tissues (27)(28)(29). In addition, there have been several clinical attempts to use molecular chaperones that can rescue wildtype P53 (30)(31)(32)(33). Because of the oncogenic role of mutant P53 (3,26), reactivation of transcriptionally inactive mutant P53 is a promising approach to cancer therapy (30).…”
Section: P53mentioning
confidence: 99%
“…In our previous reports we have established that Hsp90 rescues the WT p53 tumor suppressor protein activity at physiological temperature in a single chaperone reaction. We demonstrated that WT p53 binding to the specific DNA promoter sequence in vitro at physiological temperature is Hsp90-and ATP-dependent and that the p53 transcriptional activity in cells requires Hsp90 (25,26). WT p53 was shown to bind to Hsp90 in native or nearly native conformation (27).…”
mentioning
confidence: 99%